Misoprostol (Cytotec) for Prevention of Ovarian Hyperstimulation Syndrome. A Preliminary Investigation. - Formigli, Leonardo; Andriamaro Andriantsirombaka, Rakotobe; Rija, Ramarolahy; Badulli, Graziella; Rasoarimanana, Hanitra; Ashurova, Nargis; Krishnamoorthy, Ramachandran (Journal of Fertility Biomarkers, 2019)
This preliminary study explores misoprostol as a preventive strategy for ovarian hyperstimulation syndrome. It outlines rationale, dosing considerations, and early safety signals, and calls for controlled trials to establish efficacy and risk–benefit.
Keywords: Ovarian Hyper Stimulation; Prevention; Luteolysis; Prostaglandins; Misoprostol.